Dampak Pengembangan Pariwisata Terhadap Aspek Ekonomi Sosial dan Budaya Masyarakat di Desa Detusoko Barat Kabupaten Ende - Rimas, Yofita Elsiana; Kiak, Novi Theresia; Tungga, Cicilia Apriliani (Innovative: Journal Of Social Science Research, 2025)
This research aims to determine the impact of tourism development on the economic, social and cultural aspects of the community in Detusoko Barat Village, Ende Regency. This research is descriptive research with a qualitative approach with data collection techniques through observation, interviews and documentation. The informants used in this research consisted of the village head, village secretary, chairman of the Pokdarwis, community, tourists, head of the agriculture department, secretary of the tourism department and employees of the trade department. The research results show that the development of tourist villages has a positive impact on the community's economy, by increasing income, opening business opportunities and creating jobs. The tourism sector encourages the development of local businesses and infrastructure. However, tourism development is also faced with supporting and inhibiting factors. With good planning, tourism development in West Detusoko can have a positive long-term impact on community welfare.